Aspergillus species in ten hospitals food units from Lisbon - Viegas, Carla (2020)
The hospital environment is a source of acquired infections. Microbiologic control of hospital environments may play a role in the prevention of cross-infection. Fungal exposure in hospitals is of particular interest due to the possible patient's susceptibility. Effects due to fungal exposure are dependent on the: species present; metabolic products; concentration and exposure duration; individual susceptibility. It is important to contribute to the increase of knowledge referring to air fungal contamination in hospitals' indoor spaces, such as food units, in order to identify the most effective preventive measures to avoid such contamination. This investigation was designed to describe environmental air fungal contamination by Aspergillus species in ten hospitals' food units from Lisbon.